PENERAPAN PERLAKUAN YANG SAMA TERHADAP PASIEN DI RUMAH SAKIT SYAFIRA PEKANBARU - Sandi Yolanda; Maryati Bachtiar; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
As for what is meant by consumers in the consumer protection law are end consumers who use the product for the benefit of themselves, family, other people or other living things. Health is a basic human need to be able to live properly and productively. Health service is one of the people whose provision must be held by the government as mandated in the 1945 Constitution of the Republic of Indonesia Article 28H Paragraph 1. The establishment of Law No.34 of 2011 concerning social security that is used for the the purposes of administering effective social serucity for all Indonesian citizens is apparently not yet appropriate. In the Syafira Pekanbaru hospital, it was found that the realization of rights and obligation was not what was stated in the health law. The purpose of the thesis writing is, First, the application of the same treatment to patients in Syafira Pekanbaru hospital, Second, the efforts that can be made by the Syafira Pekanbaru hospital in improving the health services for patients.This type of reseaerch can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This is research was conducted at the Syafira hospital located in the area of Pekanbaru city Jenderal Sudirman street number 134, Tamgkerang Tengah Village, Marpoyan Damai District , while the population and sample were all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collection technique in research this is by interview, literature review and kuestionnaire.From the results of research problems there are two main things that can be concluded. First, Second,. Suggestion Writer, First, the same treatment for patients who are medical service users at the Syafira Pekanbaru hospital has not fully gone well, their obligations. This is clearly contrary to the ekisting legislation. Secondly, the efforts that can be done by Syafira Pekanbaru hospital in improving health services for patients by trying to improve the kuality of medical personnel in the hospital environment and Syafira Pekanbaru and improving medical ekuipment to help health service for the community. Suggestion Writer, First, the community should act decisively in terms of health and ask for legal protection and justice to law enforcement officers. Secondly, there is a need to socialize legal protection by the health department to the public using health services.Keywords: Patient- Same treatment- Pekanbaru.